2017
DOI: 10.1103/physrevd.95.115028
|View full text |Cite
|
Sign up to set email alerts
|

COHERENT search strategy for beyond standard model neutrino interactions

Abstract: We study the sensitivity of the stopped pion source of neutrinos at the Spallation Neutron Source (SNS) at Oak Ridge National Laboratory to neutrino non-standard interactions (NSI). In particular, we find that simple event counting above threshold can improve constraints on NSI for electron-and muon-flavored NSI, with the strongest constraints arising for flavor-diagonal NSI coupling to µ neutrinos. However, if the detector resolution is sufficient to all for even a coarse spectral study of events, COHERENT wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…For example, alterations are expected at high recoil energies of neutrino-induced interactions at direct DM detection searches [39] which on the other hand may be limited by the current uncertainties of the Atmospheric and DSNB neutrinos. Models involving light mediators are well testable at CEνNS searches and may offer a key solution to LMA-Dark [151,159] as well as implications to DM searches [28,133] and to the neutrino floor [40]. In the same spirit, combined analyses of oscillation and CEνNS data [15,18] concluded that the LMA-D solution is excluded at 3.1σ (3.6σ) for NSI with up (down) quarks.…”
Section: Connection Of Ceνns With Dark Matter Clfv Processes Andmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, alterations are expected at high recoil energies of neutrino-induced interactions at direct DM detection searches [39] which on the other hand may be limited by the current uncertainties of the Atmospheric and DSNB neutrinos. Models involving light mediators are well testable at CEνNS searches and may offer a key solution to LMA-Dark [151,159] as well as implications to DM searches [28,133] and to the neutrino floor [40]. In the same spirit, combined analyses of oscillation and CEνNS data [15,18] concluded that the LMA-D solution is excluded at 3.1σ (3.6σ) for NSI with up (down) quarks.…”
Section: Connection Of Ceνns With Dark Matter Clfv Processes Andmentioning
confidence: 96%
“…and is adopted by the COHERENT Collaboration, while in this case root mean square (rms) radius reads 133 Cs that are of interest for COHERENT, evaluated with the DSM method (not covered here), with those of the Helm, SF and KN parametrizations, is given in Ref. [36].…”
Section: Ii) Fractional Occupation Probabilities (Fop) In a Simple Shmentioning
confidence: 99%
“…We now turn our attention to frameworks beyond the SM and consider U(1) models in the presence of new mediator fields that may explain existing anomalies in B-meson decays at the LHCb experiment [69], and could also lead to the LMA-Dark solution [12,14]. While such contexts have been applied to DM searches, they may also be accessible at current and future neutrino experiments [37,39]. In fact, given the lack of an experimentally discovered signal of DM, the recent observation of CEνNS by the COHERENT experiment offers promising prospects to probe such scenarios and, moreover, to provide new insights concerning the neutrino floor at directdetection DM experiments [15].…”
Section: Vector Z and Scalar φ Mediatorsmentioning
confidence: 99%
“…We now explore novel mediator fields that could be accommodated in the context of simplified U (1) scenarios [59,60] predicting the existence of a new Z vector mediator with mass M Z [61]. Such beyond the SM interactions may constitute a new neutrino-floor at direct detection dark matter experiments [39].…”
Section: Novel Mediator Contributionmentioning
confidence: 99%